A Case for Mechanisms. Issue 1 (28th August 2015) - Künzi, Stefan A.; Sarria Toro, Juan Manuel; den Hartog, Tim; Chen, Peter
Abstract: A case study in the (re)discovery of a non‐diazo, catalytic, electrophilic cyclopropanation reaction is presented to illustrate the role of mechanistic concepts in chemical innovation. The specific instance also highlights how specific personalities interacted in the report, retraction, and reconsideration of a novel methylene transfer reaction. The case study ends with a series of lessons learned, which generalize the findings from the specific case.